On hyper-regularity and unimodularity of Ore polynomial matrices - Fritzsche, Klemens; Röbenack, Klaus (Zielona Góra: Uniwersytet Zielonogórski)
We investigate Ore polynomial matrices, i. e., matrices with polynomial entries in d/dt whose coefficients are meromorphic functions in t and as such constitute a non-commutative ring. In particular, we study the properties of hyper-regularity and unimodularity of such matrices and derive conditions which make it possible to efficiently check for these characteristics. In addition, this approach enables computation of hyper-regular left and right and unimodular inverses.
Keywords: ore polynomial matrices; hyper-regularity; unimodularity; meromorphic functions; differential operator; noncommutativity; algorithm; hyper-regular inverse